ANALISIS SISTEM INFORMASI MANEJEMEN TERHADAP KINERJA PEGAWAI PDKB – TM PADA PT PLN (Persero) AREA CIREBON - Kurniawan, Zuki; Nurnilasari, Nunung; Nasuha (Jurnal Witana, 2025)
Environmental changes and technological advancements serve as the background for PLN to continuously improve employee performance. Policy measures are needed by leveraging information technology implementation, automation policies, and centralized data management. The implementation of the PDKB Management Information System is expected to facilitate the executing unit in creating work orders that are forwarded to the PDKB team and directly monitored by management. This way, requests for network maintenance without power outages are expected to be handled more quickly and efficiently. The problem in this study is the lack of employee performance results in the PDKB-TM unit of PT PLN (Persero) in the Cirebon Area. One of the suspected factors contributing to this issue is the ineffective implementation of the management information system. The objective of this research is to analyze the implementation of the management information system, employee performance, and the impact of the management information system on employee performance in the PDKB-TM unit of PT PLN (Persero) Cirebon Area. The research method used is quantitative analysis. The study examines a specific population or sample, with data collection carried out using research instruments. The data analysis is quantitative/statistical, aiming to test predefined hypotheses. The research population consists of 80 individuals, and the expected sample size, representing 100% of the population, is equal to the total number of population members. Thus, the number of respondents in this study is 80. Based on the calculations and data analysis, the validity test results are > 0.514; the reliability test results are > 0.514; the correlation coefficient test result is 0.781, which falls into the strong category; the determination coefficient test result is 0.61 or 61%; and the linear regression equation is Y = 14.725 + 1.133X. The conclusion is that the implementation of the management information system has a strong positive relationship and a significant impact on employee performance, contributing 61% to the overall performance improvement.